Integration-Interconnection of Qur’an Function with Islamic Counseling Guidance - Khofifah, Reni; Irsyadunnas (Journal of Islamic Communication and Counseling, 2024)
The Qur'an is the holy book of Muslims, which contains knowledge about aspects of human life, a source of inspiration, and Islamic values. The urgency of the Quran is used as the main foundation in Islamic Counseling Guidance (BKI). Supposedly, BKI should be different from conventional counseling, with differences in values, techniques, and methodologies, as well as the spirit of spirituality and transcendental orientation in BKI services. The purpose of this research is to find out the integration-interconnection of the functions of the Quran with BKI. The method used in this research was a literature review. The study emphasized that functions of the Qur'an can be integrated-interconnected with the functions of BKI, including the functions of mauidhah (advice), syifa' (healing), hudan (guidance), rahmah (compassion/empathy), bayyinah (explanation), furqan (differentiator), busyra (encourager), and litukhrijannasa minnaz zulamat ilan nur (bringing the counselee out of darkness into light).